Characterization of tracheotomized patients after spontaneous subarachnoid hemorrhage. Issue 28 (10th July 2020) - Chang, Yu-Ming; Lee, Tsung-Han; Liao, Chen-Chieh; Huang, Yu-Hua
Abstract : Abstract: Spontaneous subarachnoid hemorrhage (SAH) is a catastrophic event with high disability and fatality rates. Post-SAH survivors may require prolonged intubation with the assistance of mechanical ventilators, and some patients will undergo tracheostomy to facilitate their pulmonary hygiene and airway protection. The aim of this study is to identify the incidence and risk factors of the need for tracheostomy after spontaneous SAH. We used a retrospective approach and enrolled 838 adult patients with a primary diagnosis of spontaneous SAH who survived >7 days after hospitalization. Medical information was retrieved from the administrative database utilizing diagnostic and procedure codes by the International Classification of Diseases, Ninth Revision, Clinical Modification. Patients with first-ever SAH included 329 men and 509 women, and their average age was 56.9 ± 14.4 years, ranging between 18 and 91 years. Fifty-eight of these 838 patients underwent tracheostomy procedures, and the overall incidence was 6.9%. In a multivariate logistic regression model, the independent risk factors of the need for tracheostomy were underlying diabetes mellitus ( P  = .02), hydrocephalus ( P  < .01), and pneumonia ( P  < .01). The mean duration of hospital stay was 26.0 ± 15.3 and 16.8 ± 12.2 days for patients with and without a tracheostomy, respectively ( P  < .01). In conclusion, a significant percentage of post-SAH survivors underwent tracheostomy during acute hospitalization. Attention to independent risk factors, including preexisting diabetes mellitus, concomitant hydrocephalus, and nosocomial pneumonia, is essential for timely patient selection for tracheostomy.